Evaluating Multilateral System (MLS) (gene bank) material for climate change adaptation using participatory methods with farmers and breeders - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The trials have been completed in one site -Hoima Uganda. In Hombolo & Singida In Tanzania the trials are at the second stage while in Kenya, the trials have been launched in March 2019.